Social class differences in the relationships between problem gambling and deviant behavior. Issue 1 (2nd January 2021) - Rocheleau, Gregory C.; Dennison, Christopher R; Finkeldey, Jessica G.; Reiber, Mackenzie F.
ABSTRACT: Previous studies have suggested that problem gambling is associated with various deviant outcomes. Little research, however, has considered the extent to which such relationships vary by subgroups of the population. Using data from the National Longitudinal Study of Adolescent to Adult Health ( N = 9, 644), this study examines the relationship between problem gambling in young adulthood and a range of deviant behaviors (i.e. binge drinking, marijuana use, instrumental crime, violent crime) and whether these relationships vary by family social class background. Results from logistic regressions reveal that problem gamblers have increased odds of engaging in weekly binge drinking, weekly marijuana use, and any instrumental crime. Furthermore, findings show that the relationship between problem gambling and weekly binge drinking is stronger for those from higher family social class backgrounds, but that the relationship between problem gambling and instrumental crime is stronger for those from lower family social class backgrounds. Implications of these findings are discussed.